Effect of Air Assistance, Leaf Area Density and Forward Speed on Spray Deposition in Simulated Crop Canopy - Gupta, Pankaj; Sirohi, NPS; Rengasamy, S; Vidhu, K P (Journal of Agricultural Engineering, 2004)
Efficacy of pesticides spraying is influenced by target canopy characteristics, spray equipment, mode of operation and properties of chemical. A simulated crop canopy was constructed to study effect of air velocity, leaf area density (LAD) and forward speed on deposition characteristics of an air assisted spraying system. Results showed that droplet size and droplet density on under side of the canopy was less than that on the upper side. The Air velocity, LAD and forward speed significantly influenced the droplet density on the canopy. While, higher velocities of air stream decreased the spray droplet size, the forward speed and LAD did not influence it.